Evolution of Debt Sustainability Analysis in Low-Income Countries : Some Aggregate Evidence - Baduel, Benedicte (IMF Working Papers; Working Paper ;, 2012)
The Debt Sustainability Analysis (DSA) for low-income countries (LICs) is a standardized analytical tool to monitor debt sustainability. This paper uses DSAs from three periods around the time of the global economic crisis to analyze the projected trajectories of debt ratios for a sample of LICs. The aggregate data suggest that LIC vulnerabilities improved on the whole during the period prior to the crisis, and that the crisis had a strong short-run impact on key ratios of debt (debt-to-GDP, -exports, and -fiscal revenues) and debt service (debt service-to-exports, and -revenues). Although projected debt burdens increased following the crisis, debt indicators tend to return to their pre-crisis levels over the projection horizon. This may reflect a strong and durable policy response by LICs towards the crisis, or also reflect specific assumptions on the long-run growth dividends of public external debt.